Konseling Individu: Intervensi Efektif Mengatasi Bullying dengan Pendekatan Reality Therapy - Azizah, Dewi Maulana; Hanifah, Nor; Muallifah, Muallifah (Program Studi Bimbingan dan Konseling Islam, 2024)
This study aims to analyze and examine the intervention effectiveness of individual counseling guidance services with Reality Therapy techniques in handling Bullying cases at school. Bullying is caused by inequality between students in physical and mental terms. The act of Bullying becomes a habit due to a lack of awareness in students of the behavior and impact of Bullying to deal with the impact of Bullying in schools, counselors provide individual counseling guidance services with Reality Therapy techniques. A qualitative approach with case study research is used in this research. This study uses data collection techniques in the form of a questionnaire distributed via google form. The use of Reality Therapy techniques in individual counseling guidance is able to have a positive impact on students, by making them aware of the consequences of their behavior and the responsibility of each act of Bullying. The effectiveness of the impact of individual counseling guidance services with Reality Therapy techniques shows good and significant results on students who are the behavior and victims of Bullying. The importance of the success of counseling guidance services is certainly also influenced by the collaboration between teachers, principals and parents.